(untitled) (International Journal of Food and Nutritional Sciences, 2021)
The Hospitality and Tourism industry is characterized by its dynamic nature, high customer expectations, and a diverse workforce. This review explores the Human Resource Management (HRM) practices within this industry, highlighting their significance in shaping organizational success and guest satisfaction. Drawing from an extensive body of literature, this review examines key HRM areas, including recruitment and selection, training and development, performance management, employee engagement, and talent management. It also delves into the transformative role of technology in enhancing HRM practices. By analyzing empirical studies, case examples, and best practices, this review underscores the evolving landscape of HRM in Hospitality and Tourism, emphasizing the need for innovative and strategic approaches to meet the industry’s unique challenges and opportunities. As the industry continues to grow and adapt to global trends, HRM practices remain at the heart of fostering a skilled, engaged, and customer-focused workforce. This paper explores the dynamic landscape of Human Resource Management (HRM) practices in the Tourism and Hospitality industry, focusing on the role of innovation in shaping the future of HRM.